Assessing causes of contractual disputes from different type of condition of contracts - Che Haron, Roziha; Nasid Masrom, Md Asrul; Kamal, Khairani (Penerbit UTHM, 2021)
In a construction industry, a Condition of Contract (CoC) is primarily used to ensure a project can be delivered successfully with minimum disputes. The contractual disputes rooted from many factors, including from the improper management of conflict between parties in the project, misinterpretation of the CoC, lack of documentation, and discrepancies and ambiguities of documents which may lead to as cost overruns, project delay and project cashflow. Thus, a comprehensive CoC plays a significant role to express the rights and obligations of the main contracting parties. CoC functions in stating to each party on what they shall do and to the extent of their entitlement of rights and obligations under the contract. Despite having various of published CoC such as PAM Contract and series of PWD Form of Contract to govern the construction projects, numerous construction cases in relation to contractual disputes are still increasing over the years and there has been little discussion about the causes of disputes. It indicates the ineffectiveness of the contract provision in the CoC. Hence, this study presents thorough review of the disputes occurs in the construction industry by outlining the issues raised in the court cases. This scenario has paved this paper to achieve the objectives of the research, including to identify the factors attribute to the construction dispute and to investigate the provision in CoC that caused the contractual disputes. The data collection used was mainly through literature synthesis and surveys. The results revealed that there are five attributes of construction disputes. The findings of the paper would be beneficial to practitioners in increasing their awareness of the flaws in the CoC and could be helpful in mitigating the disputes.